Analysis of the Suitability of Stopping Distance and Side Clearance at Curves in Relation to Speed Using the Road Construction Method - Irawan, Faisal Akbar; Ar Rasyid, Muhammad Hisyam; Puspitaningrum, Anggita Suci; Fakhrudi, Alfyan Cana Dwi; Hadi, Suprapto; Baharuddin, Alfan (Riwayat: Educational Journal of History and Humanities, 2025)
The analysis results show that several road curves still fail to meet the required safety standards. Field measurements indicate that only ten curves satisfy the stopping sight distance (SSD) criteria, while twenty-four curves experience SSD deficiencies, with the largest shortfall occurring at STA 13+800 northbound. Lateral clearance evaluation also shows limited compliance, with only five curves meeting the standard and twelve curves identified as having significant shortages most notably at STA 13+900. Several locations are categorized as hazard points because they exhibit deficiencies in both SSD and lateral clearance. Overall, inadequate lateral clearance is found to directly reduce available sight distance due to visual obstructions near the travel lane, indicating that geometric improvements are necessary to enhance safety along the PemalangRandudongkal corridor.